Demands and stress before and during the COVID-19 pandemic of parents to children with autism spectrum disorder - Sartor, Teresa; Sons, Sarah; Kunina-Habenicht, Olga; Tröster, Heinrich; Kuhn, Jörg-Tobias (Frontiers in Psychology, 2023)
Parents to children with Autism Spectrum Disorder (ASD) face diverse daily demands that can lead to stress. The aim of this study was to examine to which extent stress in parents to children with ASD can be explained by daily demands before and during the COVID-19 pandemic (after lockdowns; first half of 2022), and whether there are differences between the two time periods in this regard. Data from parents to children with ASD living in Germany from two independent questionnaire studies (before the pandemic: N = 168, during the pandemic: N = 105) were matched for comparability. Simple and multiple linear regression analyses were used to answer the research question. Parental stress as well as all demands examined showed higher levels during the COVID-19 pandemic than before. Significant predictors of parental stress before and during the COVID-19 pandemic were 1) the daily demands to deal with the child's problem behavior, 2) the restriction of one's personal way of life, and 3) the challenge to cooperate with the partner. During the COVID-19 pandemic, the child's problem behavior was particularly relevant. It was also found that the demand to deal with stigmatizing reactions did not explain parental stress during the COVID-19 pandemic whereas before the pandemic it had been a significant predictor. Although parental stress and the demands of daily life increased during the pandemic, most of the stress can be explained by the same demands. It is suggested that the increased levels may be due to an increase in the child's ASD symptomatology, which is why it is advisable to install therapeutic and care structures that prepare children with ASD for future crises.